An exploration of the impact of educational background on basic science and life sciences librarians. - Lipke, Laura; Hoogland, Margaret A.; Kupsco, Jeremy; Schulte, Stephanie J. (Medical Reference Services Quarterly)
This study sought to investigate the influence of a science educational background on librarian interactions with basic and life sciences programs. Through semi-structured interviews with 14 librarians, the study identified several key themes: understanding and enjoying science is beneficial; previous experience influences librarians' approaches; relationships are important; defining success is challenging; and collaborating with other campus units is unusual. Results suggest a science undergraduate or graduate degree and previous science-related work experience enhance librarians' comfort and communication with scientists and highlight a lack of professional continuing education related to researcher workflows.